Process Intensification: Activated Carbon Production from Biochar Produced by Gasification Highly porous carbon substances with low production costs - Erdem, Ahmet; Dogru, Murat (Johnson Matthey Publ Ltd Co, 2021)
The recent increase in the number of policies to protect the environment has led to a rise in the worldwide demand for activated carbon, which is the most extensively utilised adsorbent in numerous industries and has a high probability to be used in the energy and agriculture sectors as electrodes in supercapacitors and for fertiliser production. This paper is about the production of activated biochar from oak woodchips char generated by an updraft fixed bed gasifier reactor. Following this, using steam as activating agent and thermal energy from produced synthesis gas (syngas), the resulting highly microporous carbonaceous biomaterial was subjected to physical activation at 750 degrees C. The properties of activated biochar include adsorption or desorption of nitrogen to identify the physical adsorption and surface area measurement, thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The biochar surface area, generated as a result of the gasification process, showed substantial improvement after steam activation. Also, significant discrepancies were obtained from the surface volume and areas of biochar byproducts from the gasifier and activated biochar obtained by steam activation after the gasification treatment (total pore volume 0.022 cm(3) g(-1) and 0.231 cm(3) g(-1), Brunauer-Emmett-Teller (BET) surface area 21.35 m(2) g(-1) and 458.28 m(2) g(-1), respectively). The two samples also yielded noteworthy differences in performance. As a consequence, it may be concluded that the kinetics of steam gasification is quicker and more efficient for the conversion of biochar to activated carbon. The pore sizes of the carbon produced by steam activation were distributed over a wide spectrum of values, and both micro- and mesoporous structures were developed.
Keywords: Steam Activation; Physical Activation; Removal; Water; Dioxide; Chars; Wood; Soil; Co2